PENGUJIAN PECKING ORDER THEORY DI PERUSAHAAN PERBANKAN INDONESIA - Khairul Amal, Nasir Azis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2016)
ABSTRACTThe purpose of this research was to determine the effect of profitability on leverage in the company, the effect the structure of the assets to leverage on the company, the effect of growth companies to leverage on the company, the size of the company to leverage on the company and to determine the effect of profitability, asset structure, the company's growth and size of the company to leverage on the company. This research was conducted in the Indonesia Stock Exchange  located at Jl. Sudirman Kav. 52-53, Jakarta 12190. The object of this study is profitability, asset structure, growth, and size as the independent variable and leverage as the dependent variable of the companies belonging to the banking company's shares on the Indonesia Stock  Exchange. The research proves that the profitability variable values obtained tCountby 2,757 while tTable stand with 2,045, the result of this calculation indicates that tCounttTable with a significance level of 0.011, variable asset structure obtained the value of tCountby 3,037, while tTable stand with 2,045, the result of this calculation indicates that tCounttTable with a significance level of point by 0.006, Growth Opportunities Variable obtained the tCountamounted to 2.428 while the tTablevalue just 2.045, the result of this calculation indicates that tCounttTable with a significance level of point by 0.023, while the size of company variable obtained the value of tCount by 1,028, while tTable stand with 2,045, the result of this calculation indicates that tCounttTable with a significance level of point by 0.314.Keywords: Profitability, Asset Structure, Growth, Company Size and Leverage